Comparison of Omega-3 Serum Level Between Hiv-Aids Patients Along with Their Clinical Profiles and Healthy Population in Mohammad Hoesin General Hospital Palembang - Lidiawati Handayani; Harun Hudari; Eddy Mart Salim; Erial Bahar; Nova Kurniati; Zulkhair Ali; Ferry Usnizar (HM Publisher, 2021)
Introduction. Human Immunodeficiency Virus (HIV) infection has been a concerning health problem worldwide. It causes reduction in body immune system and inflammation that can affect its clinical profile. Undergoing ARV therapy patients causes intestine microbiota dysbiosis and translocation that lead to imperfect absorbtion of fatty acid. One way to control microbiota dysbiosis is by controlling the nutritional factor, especially with omega-3. However, different regions upstands different custom in fish consumption especially those of which are rich in omega-3. The purpose of this research is to compare omega-3 serum level between HIV-AIDS patients and healthy population, as well as analyzing the correlation of omega-3 serum level with of HIV-AIDS patient clinical profile.Methods. The research will be applying observational analytic study using comparative study approach which will be performed in Tropical Infection Internal Medicine polyclinic and Medical Check-Up Polyclinic in RSMH Palembang starting from April 2020 until January 2021. Sample consisted of 32 HIV-AIDS patients from 20-58 years of age and 16 healthy population from 27-35 years of age on whom will be performed physical examination as well as clinical profile and omega-3 serum level examination. All data processing and analysis will be performed using SPSS v.25 for windows.Results. Out of 32 HIV-AIDS patients, we obtained low omega-3 serum level with median value at 3 (2-4) Umol/L, while in healthy population was 4 (3-6) Umol/L. Multivariate analysis inferred that the lower omega-3 serum level correlated with HIV-AIDS stage, duration of ARV therapy, blood pressure, and sex.Conclusion. Omega-3 serum levels in HIV-AIDS patients were lower than the healthy population. There was a correlation between omega-3 serum levels and their clinical profile of HIV-AIDS patients in Mohammad Hoesin General Hospital Palembang.